Literary Images of the Great Exhibition of 1851 - Šteflová, Veronika (Univerzita Pardubice, 2022)
The bachelor thesis introduces and analyses the images of the Great Exhibition of 1851 in two literary sources; Mrs. Napier's poem The Lay of The Palace and Henry Mayhew's novel 1851: or, The Adventures of Mr. And Msr. Cursty Sandboys. To understand both the nuances and the parallels between the event's impressions depicted in these literary sources, the theoretical part provides historical, social and cultural background of the Victorian era in Great Britain. Additionally, the Exhibition is introduced simultaneously with the contexts mirroring the historical setting in order to illustrate the event's complexity.
Literární obrazy Světové výstavy 1851
Keywords: Světová výstava; Velká Británie; Viktoriánské období; Křišťálový palác; devatenácté století; Great Exhibition; Great Britain; Victorian era; Crystal Palace; nineteenth century